Exploring factors and trends in place of death by cancer: a population-based study in BrazilResearch in context - Jessé Lopes da Silva; Sarah Ananda Gomes; Lívia Costa de Oliveira; Lucas Zanetti de Albuquerque; Lívia Machado Moura; Luiz Claudio Santos Thuler; Andréia Cristina de Melo (Elsevier, 2024)
Summary: Background: The place of death profoundly affects end-of-life care quality, particularly in cancer. Assisting individuals at home enhances support, privacy, and control, reducing healthcare costs. This study seeks to elucidate factors associated and trends in place of death by cancer in Brazil. Methods: Using data obtained from the National Mortality Information System, this study extracted tumour topography, sociodemographic characteristics, and the place of death (outcome classified into hospital or home death) by cancer in Brazil from 2002 to 2021. Findings: The analysis included 3,677,415 cases, with 82.3% of deaths occurring in hospitals and 17.7% at home. Most participants were male (53.1%), had gastrointestinal tumours (32.2%), and resided in the Southeastern region (48.7%). Home deaths were more frequent in the Northeastern (30.2%) and Northern (24.8%) regions compared to the Southern (17.1%) and Southeastern (12.2%) regions. A strong inverse correlation was found between home deaths and the Human Development Index of the region. Over the years, there was a reduction in home deaths, followed by a recent increase. Individuals with no formal education, indigenous individuals, and patients from the North, Northeast, and Central-West regions had higher rates of home deaths, while patients with haematological malignancies had lower rates compared to those with gastrointestinal tumours. Interpretation: The minority of deaths by cancer in Brazil occur at home, with distinct trends over time. Home death was associated with regional, racial and educational level differences. Funding: No funding.